Predicting criminal activities analyzing video signal using machine learning - Sadman, Syed Md.; Kabir, Tabassum; Mostafa, Nairita; Chowdhury, Ahmed Ashik (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2020.